THE USE OF TOTAL PHYSICAL RESPONSE METHOD TO IMPROVE ENGLISH VOCABULARY MASTERY FOR THE FIFTH GRADE STUDENTS OF SDN II LOGANDU IN THE ACADEMIC YEAR OF 2015/2016 - Nurjanah, Rosita (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The use of Total Physical Response Method to Improve English Vocabulary Mastery for the Fifth Grade Students of SDN II Logandu in the Academic Year of 2015/2016. The objectives of this research is to improve  vocabulary mastery of English using Total Physical Response methodabout Healthy habits and At the school at the fifth grade students of SDN II Logandu in the academic year of 2015/2016.This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. Subjects of the research were 21 students of the fifth  grade of SD Negeri II Logandu in academic year of 2015/2016. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique. Sources of data were derived from students, fifth grade class teacher, observer, and document. Techniques of collecting data were test, interview, observation, and documentation. The results showed that the application of Total Physical Response method can improve English vocabulary mastery on Healthy Habits and At The Schoolfor the fifth grade students of SDN II Logandu in the academic year of 2015/2016. Keywords: Total Physical Response, English, vocabulary